Pro-recombination Role of Srs2 Protein Requires SUMO (Small Ubiquitin-like Modifier) but Is Independent of PCNA (Proliferating Cell Nuclear Antigen) Interaction - Kolesar, Peter; Altmannova, Veronika; Silva, Sonia; Lisby, Michael; Krejci, Lumir (The Journal of biological chemistry, 2016)
Srs2 plays many roles in DNA repair, the proper regulation and coordination of which is essential. Post-translational modification by small ubiquitin-like modifier (SUMO) is one such possible mechanism. Here, we investigate the role of SUMO in Srs2 regulation and show that the SUMO-interacting motif (SIM) of Srs2 is important for the interaction with several recombination factors. Lack of SIM, but not proliferating cell nuclear antigen (PCNA)-interacting motif (PIM), leads to increased cell death under circumstances requiring homologous recombination for DNA repair. Simultaneous mutation of SIM in asrs2ΔPIMstrain leads to a decrease in recombination, indicating a pro-recombination role of SUMO. Thus SIM has an ambivalent function in Srs2 regulation; it not only mediates interaction with SUMO-PCNA to promote the anti-recombination function but it also plays a PCNA-independent pro-recombination role, probably by stimulating the formation of recombination complexes. The fact that deletion of PIM suppresses the phenotypes of Srs2 lacking SIM suggests that proper balance between the anti-recombination PCNA-bound and pro-recombination pools of Srs2 is crucial. Notably, sumoylation of Srs2 itself specifically stimulates recombination at the rDNA locus.
Keywords: SUMO-1 Protein; proliferační antigen buněčného jádra; rekombinace genetická; DNA Helicases; Recombination, Genetic; protein SUMO-1; DNA fungální; sumoylace; Amino Acid Motifs; Saccharomyces cerevisiae Proteins; DNA-helikasy; Saccharomyces cerevisiae - proteiny; aminokyselinové motivy; DNA, Ribosomal; Proliferating Cell Nuclear Antigen; protein-protein interaction; homologous recombination; DNA repair; oprava DNA; DNA, Fungal; ribozomální DNA; small ubiquitin-like modifier (SUMO); Sumoylation; proliferating cell nuclear antigen (PCNA); DNA Repair